2009
DOI: 10.1111/j.1540-627x.2008.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowledge Resources on New Venture Performance

Abstract: A new venture's strategy-and thus its performance-is based upon the knowledge the firm has about its market, its opportunity in that market, and its appropriate conduct to take advantage of that opportunity. Resource-based theory underscores knowledge as a type of resource that confers competitive advantage and the potential for sustainability, two factors that are critical for start-ups. Three types of procedural knowledge are considered to be important at start-up: (1) about the industry in which the venture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 84 publications
7
193
0
3
Order By: Relevance
“…Tanriverdi and Venkatraman [55] proposed that corporate performance is improved when the firm simultaneously exploits three types of knowledge relatedness, which are product, customer and managerial knowledge relatedness. West and Noel [56] found that knowledge relatedness with respect to the type of business is positively associated with performance. We call the extent to which the business idea aligns with the actors' knowledge relatedness.…”
Section: Knowledge Relatednessmentioning
confidence: 99%
“…Tanriverdi and Venkatraman [55] proposed that corporate performance is improved when the firm simultaneously exploits three types of knowledge relatedness, which are product, customer and managerial knowledge relatedness. West and Noel [56] found that knowledge relatedness with respect to the type of business is positively associated with performance. We call the extent to which the business idea aligns with the actors' knowledge relatedness.…”
Section: Knowledge Relatednessmentioning
confidence: 99%
“…1, Mar. 2015 performance level increasing with the entrepreneur's level of education (Honig, 1998;West & Noel, 2009;Headd, 2003;Van Praag, 2003). The explanation of this phenomenon lies in the capacity of a better education to help the acquisition and transformation of know-how (Haber & Reichel, 2005), which, in turn, helps entrepreneurs assess opportunities and use resources more efficiently (Castrogiovanni, 1996).…”
Section: Survival In the Long Runmentioning
confidence: 99%
“…Entrepreneurs with a background in the academic disciplines of science, technology, engineering and mathematics (the so-called STEM disciplines) tend to focus on the technical aspects of their business idea . The 'technical mindset' of STEM entrepreneurs can impede their focus on value for the customer, which in turn causes a 'management' or survival challenge for the novel business opportunity (West & Noel, 2009;Schindehutte, Moris & Kocak, 2008). With this study we aim to contribute to the literature in the following ways.…”
Section: R30: What Has Also Been a Very Important Theme For Me Is -Hamentioning
confidence: 99%
“…The ensuing predominantly 'technical mindset' can impede the entrepreneur's focus on value for the customer, which in turn causes a 'management' or survival challenge of the novel business opportunity (West & Noel, 2009;Schindehutte, Moris & Kocak, 2008). There is a basic training on business modeling which lasts one afternoon and is offered at least twice during the one-year program.…”
Section: R30: What Has Also Been a Very Important Theme For Me Is -Hamentioning
confidence: 99%
See 1 more Smart Citation